Model Analysis of Job Satisfaction in Nurses - Rokhayati, Yuli; Samino, Samino; Irianto, Torry Duet (Sarana Ilmu Indonesia (salnesia), 2025)
Job satisfaction reflects how much employees like or dislike various aspects of their work. At RSUD Dr. H. Bob Bazar SKM, many nurses expressed dissatisfaction: 52,4% with income, 38,1% with working conditions, 52,4% with promotion opportunities, 57,1% with the work itself, 52,4% with recognition, 57,1% with work experience, and 71,4% with both self-development and overall job satisfaction. This dissatisfaction impacts nurses’ performance. This study aimed to determine a job satisfaction model among nurses at RSUD Dr. H. Bob Bazar SKM, South Lampung. It used a cross-sectional analytic design with a qualitative approach, involving all 149 nurses as subjekts through total sampling. Data were collected using questionnaires and analyzed using Smart PLS (Partial Least Squares). The modified model showed all latent variable constructs had good discriminant validity, and the AVE test indicated no issues with convergent validity. Bootstrapping analysis revealed that among eight exogenous variables, only self-development and promotion opportunities significantly affected job satisfaction (p-value<0,05; t>1,96). The R² value of 0,701 suggests that these two variables can explain 70,1% of job satisfaction. Self-development was measured with five indicators (highest t=13,836), promotion opportunities with five indicators (highest t=15,576), and job satisfaction with six indicators (highest t=15,285). The study recommends the hospital prioritize improving self-development and promotion opportunities to enhance job satisfaction, contributing to better planning and organizational growth.